Phenomenology Study on Health Related Quality Of Life On People With HIV/AIDS at Victory Yogyakarta - handayani, Lutfi; Chairiyah, Royani; Triratnawati, Atik (International Journal of Health Literacy and Science, 2024)
Background: HIV/AIDS is a disease that continuosly develops and becomes global health problem either in advanced or developed country. The condition transformation of chronic HIV patients can be handled by improving Health Related Quality of Life (HRQOL). HRQOL program becomes an important focus of WHO aiming to improve the society quality in maintaining the level human health. Research Purpose: To know Health Related Quality of Life on ODHA at Victory Foundation Yogyakarta related to physical, psychological, mental-emotional, and religious aspect at Victory Plus Foundation Yogyakarta. Method: This research used qualitative research method with phenomenology approach. The information was obtained through deep interview technique and observation on eight ODHA informants. Results: The result of HRQOL qualitative analysis on ODHA is based on four various aspects. Based on physical aspect, obtained skin rash, reddish spots, whitened or blackened scars, initial symptom of depression, and mayor depression. The mental-emotion of informants gets better after 1-3 months of psychological guidance accompanied by ARV treatment. Religious aspect obtained improvement before and after recognizing ODHA status. Research Conclusion: HRQOL on ODHA is based on four aspects such as physics, psychology, mental-emotion, and religion and it is already well done after obtaining guidance in health service quality.